Enabling change through Education for Children and their Families Experiencing Vulnerability and Disadvantage: The Understandings of Early Childhood Professionals. Issue 2 (May 2015) - Roberts, Wendy
CHILDREN HAVE AN INALIENABLE right to an education and it is in early childhood that we build the foundations for learning and development. Social inclusion, access, participation and engagement are key to early learning success, a time integral to overall health, wellbeing and future role in society. Children experiencing vulnerability and disadvantage have a high tendency for low educational outcomes. Currently, government policy argues that facilitating change through education can break the cycle of disadvantage and transform the lives of the individual child, their families and the wider community. This qualitative phenomenological study seeks to identify the enablers and barriers in early childhood education and care encountered by its professionals at the 'frontline' perspective. Change Ideas is a process by which the humanitarian ideals of a society supports its most vulnerable and disadvantaged, via education, enacting rights as self-actualising human beings through supportive and well-informed everyday practice.